PENGARUH IBADAH PERJAMUAN KUDUS TERHADAP PERTUMBUHAN KEROHANIAN JEMAAT GMAHK BUNSADAN KOTA MARUDU SABAH, MALAYSIA BERDASARKAN 1 KORINTUS 11:27 - Enos Hitlor; Alvyn C. Hendriks (Jurnal Koinonia, 2020)
In writing this thesis, the author tries to examine the effect of the Holy Communionservice on the spiritual growth of the GMAHK Bunsadan Kota Marudu Sabah Cityof Malaysia congregation based on 1 Corinthians 11:27. This research is based onfour indicators: The theological understanding of the word "unworthy" in 1Corinthians 11:27; how to attend the Lord's Supper to be considered worthy; theimpact of the Holy Communion Service on the spirituality of the members of thecongregation and the views of the experts on the spiritual growth in the HolyCommunion. This research is divided into two main parts, which is theoreticalresearch and field research. From the result of theoretical research, the meaning ofthe word improper can be found in 1 Corinthians 11:27 where it refers to eating anddrinking as the Corinthians did, who ate it not referring to the death of Jesus Christ'ssacrifice (without respect), but in a manner like the Israelites made the Passover ,which they celebrate as a reminder of their liberation from Egyptian slavery. The onewho is deemed worthy to attend the Holy Communion service are those who havebeen baptized and are following the worship according to the Adventist Church's rulebook. There are several benefits of attending the Holy Communion service which arecommemorating His sacrifice, being humble, reconciling and developing the Spirit ofservice. Experts say that this Holy Communion service is very important because itencourages God's people to have an ethical life according to God's word and live aspiritual life. In the field research, the results of the respondents provide informationthat all statements contained in the questionnaire (P1 - P20) are well understoodexcept for statements P1 - P5 where the respondent gives a hesitant answer.Overcoming this, the writer will give a seminar in connection with the writing of thisthesis.